An electrode, and a method of making and using the same
Patent Information
- Application Number
- CN202411245827.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-09-05
AI Technical Summary
但是,铜在空气中容易被氧化,这导致相应铜浆在应用中电阻容易逐渐升高,限制了铜浆的广泛应用
[0018]本申请所述的电极,利用抗氧化性较优的片状铜粉,以接近水平状态或者水平状态贴敷于电极的表面,提高电极整体在空气中放置时的抗氧化性,降低电极的电阻率。进一步利用片粉和球粉的形状差异,通过控制片状铜粉在电极表面的表面积占比,提高片粉在表面贴敷的牢固性和确保电极具有较高的铜粉填充率,进一步降低电极的电阻率。
Smart Images

Figure BDA0005031201390000041 
Figure BDA0005031201390000111 
Figure BDA0005031201390000121
Abstract
Description
Technical Field
[0001] This application relates to the field of solar cells, specifically to an electrode, its preparation method, and its application. Background Technology
[0002] In the 21st century, humanity has become increasingly reliant on electronic information products. These products consist of a variety of components. Currently, electronic pastes are one of the fundamental materials for the development of electronic components towards lightweighting, miniaturization, environmental friendliness, and low cost. Electronic pastes can be used to manufacture electronic components such as electrodes, wires, capacitors, inductors, and resistors, and are widely used in numerous fields including electronic computers, aerospace, automotive, and communications. Conductivity is one of the important parameters for evaluating the quality of electronic pastes. Conductive pastes, as a crucial component of solar cells, play a vital role in improving cell efficiency. However, conductive silver paste is the mainstream conductive paste on the market, causing the cost of solar cells to remain high. If copper paste could be used instead of silver paste for the grid lines of solar cells, the cost would decrease significantly.
[0003] Among many base metals, copper is inexpensive, does not have the problem of electron migration, and has high conductivity, making it the best alternative to silver conductive fillers. However, copper is easily oxidized in air, which causes the resistance of the corresponding copper paste to gradually increase during application, limiting its widespread use. Summary of the Invention
[0004] This application aims to provide an electrode that is not easily oxidized, has low resistivity, and high conductivity.
[0005] This application provides an electrode comprising sheet-like copper powder and spherical copper powder, wherein the surface of the sheet-like copper powder is attached to the electrode surface in a substantially horizontal state.
[0006] Furthermore, the flake copper powder is arranged at an angle α to the surface of the electrode, where 0°≤α≤45°.
[0007] Furthermore, the projected area of the sheet-like copper powder applied to the electrode surface accounts for 30%-70% of the electrode surface area. Furthermore, the mass ratio of the sheet-like copper powder to the spherical copper powder is (0.7-2):1.
[0008] Furthermore, the thickness D50 of the flake copper powder is 100-500 nm, and its diameter D50 is 1-10 μm.
[0009] Furthermore, the particle size D50 of the spherical copper powder is 100-500 nm.
[0010] Furthermore, the tap density of the flake copper powder is 4.4–5 g / ml, and the tap density of the spherical copper powder is 4.3–4.9 g / ml.
[0011] Furthermore, the specific surface area of the flake-shaped copper powder is 0.3–0.8 m². 2 / g, the specific surface area of the spherical copper powder is 2.5-3.0m². 2 / g.
[0012] Furthermore, the cross-section of the electrode is trapezoidal or trapezoidal, and the cross-section is perpendicular to the extension direction of the electrode.
[0013] Furthermore, the electrode is prepared by screen printing.
[0014] Furthermore, the electrode also includes copper nanoparticles, each comprising at least two interconnected copper nanoparticles connected by surface contact.
[0015] Furthermore, the nano-copper particles are linear copper particles formed by at least two interconnected copper nanoparticles, and / or
[0016] The copper nanoparticles are formed by bending and connecting at least two connected copper nanoparticles at a certain angle to form L-shaped copper particles, V-shaped copper particles, U-shaped copper particles, triangular copper particles, quadrilateral copper particles, W-shaped copper particles, or polygonal copper particles with more than 5 sides.
[0017] This application also provides a solar cell, wherein the aforementioned electrodes are included.
[0018] The electrode described in this application utilizes flake-shaped copper powder with superior oxidation resistance, which is applied to the electrode surface in a near-horizontal or horizontal manner. This improves the overall oxidation resistance of the electrode when placed in air and reduces its resistivity. Furthermore, by utilizing the shape difference between flake and spherical powders and controlling the surface area ratio of the flake-shaped copper powder on the electrode surface, the adhesion of the flake powder to the surface is improved, ensuring a high copper powder filling rate and further reducing the electrode's resistivity. Attached Figure Description
[0019] Figure 1 This is a scanning electron microscope image of spherical copper powder placed in air.
[0020] Figure 2 This is a scanning electron microscope image of sheet-like copper powder placed in air.
[0021] Figure 3 A scanning electron microscope image of one electrode embodiment of this application.
[0022] Figure 4This is a 3D microscope image of the electrode.
[0023] Figure 5 This is a 3D microscope image of the electrode.
[0024] Figure 6 This is a scanning electron microscope image of another electrode embodiment of this application.
[0025] Figure 7 This is a scanning electron microscope image of the electrode in Example 1. Detailed Implementation
[0026] The following description provides exemplary embodiments of this application, including various details to aid understanding, and should be considered merely exemplary. Therefore, those skilled in the art will recognize that various changes and modifications can be made to the embodiments described herein without departing from the scope and spirit of this application. Similarly, for clarity and brevity, descriptions of well-known functions and structures are omitted in the following description.
[0027] In this application, the electrode comprises copper powder of different diameters and shapes. Spherical copper powder has a large specific surface area and high surface activity, but its oxidation resistance is weaker. In comparison, flake-shaped copper powder has stronger oxidation resistance. Figures 1-2 It can be seen that after spherical copper powder and flake copper powder are placed in the air for a period of time, an oxide layer forms on the surface of the spherical copper powder, while the surface of the flake copper powder remains almost unchanged. Figure 1 a represents the initial morphology of the spherical copper powder. Figure 1 b represents the morphology after being left for a period of time. Figure 2 a represents the initial morphology of the flake-like copper powder. Figure 2 (b shows the morphology after a period of time). To obtain an electrode with excellent electrical properties, the particle size, shape, and quantity of copper powder need to be adjusted to improve the filling rate of copper powder in the electrode and ensure high oxidation resistance.
[0028] Therefore, this application provides an electrode comprising sheet-like copper powder and spherical copper powder, wherein the surface of the sheet-like copper powder is adhered to the electrode surface in a substantially horizontal state. Figure 7 It can be seen that the sheet copper powder is applied to the electrode surface in a basically horizontal state. The electrode surface at this point refers to the tangent of the electrode surface where the sheet copper powder intersects with the electrode.
[0029] In the electrode of this application, sheet-like copper powder with excellent oxidation resistance is applied to the surface of the electrode in a near-horizontal or horizontal state to improve the overall oxidation resistance of the electrode when placed in the air and reduce the resistivity of the electrode.
[0030] Furthermore, the flake-shaped copper powder is arranged at an angle α to the surface of the electrode, where 0°≤α≤45°, in combination with... Figure 3 It can be seen that α is the tilt angle of the sheet-like copper powder on the electrode surface relative to the electrode surface.
[0031] In this paper, the α angle is measured using SEM (Scanning Electron Microscopy). A sheet of copper powder within the field of view is selected, and the midpoint of the intersection line between the horizontal plane of the sheet of copper powder and the electrode surface is chosen. A tangent line is drawn on the electrode surface using this midpoint, and the angle between the horizontal plane of the sheet of copper powder and this tangent line is calculated to obtain an α angle. The same method is used to measure the α angle of more than 10 sheet of copper powder in different regions of the test sample, and the average value of all measured α angles is calculated. Those skilled in the art will understand that the above method is merely exemplary, and they can appropriately reduce or increase the selected test sample area or number based on actual circumstances.
[0032] In some implementations, 0°≤α≤40°.
[0033] In some implementations, 0°≤α≤35°.
[0034] In some implementations, 0°≤α≤30°.
[0035] In some implementations, 0°≤α≤25°.
[0036] In some implementations, 5°≤α≤40°.
[0037] In some implementations, 5° ≤ α ≤ 35°.
[0038] In some implementations, 5° ≤ α ≤ 30°.
[0039] In some implementations, 5°≤α≤25°.
[0040] Specifically, α can be 45°, 42°, 40°, 38°, 35°, 32°, 30°, 28°, 25°, 22°, 20°, 18°, 15°, 12°, 10°, 8°, 5°, etc.
[0041] Furthermore, the area of the orthographic projection of the sheet-like copper powder applied to the electrode surface accounts for 30%-70% of the electrode surface area.
[0042] In the electrode of this application, the shape difference between sheet powder and ball powder can be further utilized to control the surface area ratio of sheet copper powder on the electrode surface, thereby improving the firmness of sheet powder on the surface and ensuring that the electrode has a high copper powder filling rate, and further reducing the resistivity of the electrode.
[0043] In this paper, the projected area of the sheet-like copper powder on the electrode surface is obtained by SEM (scanning electron microscopy). The electrode surface area is obtained by 3D microscopy, which measures the shape and size of the electrode to calculate its surface area. For example, when the electrode is the grid line of a solar cell, such as... Figure 4 as well as Figure 5 As shown, the cross-section of the electrode is trapezoidal or trapezoidal, and this cross-section is perpendicular to the extension direction of the electrode. The upper base a, lower base b, and height h of the trapezoid, as well as the length l of the electrode, are measured. The surface area of the electrode is then calculated using the following formula:
[0044]
[0045] Specifically, the area of the orthogonal projection of the sheet-like copper powder on the surface of the electrode to the surface area of the electrode can be 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, etc.
[0046] The mass ratio of flake copper powder to spherical copper powder is (0.7-2):1. By controlling this ratio, a high copper powder filling rate is ensured in the electrode, improving its oxidation resistance. If the flake powder content is too low, the electrode's oxidation resistance will decrease, and its electrical performance will degrade after light irradiation. If the flake powder content is too high, the flake powder on the electrode surface cannot be evenly arranged, increasing the angle between the powder and the electrode, which negatively impacts both the electrode's oxidation resistance and density.
[0047] The thickness D50 of the flake-shaped copper powder is 100-500 nm, for example, it can be 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, etc., and its diameter D50 is 1-10 μm, for example, it can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, etc. The particle size D50 of the spherical copper powder is 100-500 nm, for example, it can be 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, etc.
[0048] 500nm, etc.
[0049] In this paper, D50 refers to the particle size at which the cumulative particle size distribution percentage of a sample reaches 50%. Physically, it means that 50% of the particles are larger than D50, and 50% are smaller. D50 is also called the median diameter or median particle size.
[0050] D50 is measured using SEM (Scanning Electron Microscopy). Ten different regions of the test sample are photographed. For each photograph, ten flake-like copper powder particles are observed, and their diameter is measured along the diameter direction. The median value is then calculated, which is the D50 of the diameter. Similarly, the thickness is measured along the thickness direction, and the median value is calculated, which is the D50 of the thickness. For each photograph, ten spherical copper powder particles are observed, and their diameter is measured. The median value is then calculated, which is the D50 of the spherical copper powder particle size. Those skilled in the art will understand that the above method is merely exemplary, and they can appropriately reduce or increase the number or area of the selected test sample based on actual circumstances.
[0051] In this application, the tap density of the flake copper powder is 4.4–5 g / ml, and the tap density of the spherical copper powder is 4.3–4.9 g / ml. The specific surface area of the flake copper powder is 0.4–0.7 m². 2 / g, the specific surface area of the spherical copper powder is 2.5-3.0m². 2 / g.
[0052] Specifically, the tap density of the flake copper powder can be any value between 4.4 g / ml, 4.5 g / ml, 4.6 g / ml, 4.7 g / ml, 4.8 g / ml, 4.9 g / ml, and 5 g / ml.
[0053] Specifically, the tap density of the spherical copper powder can be any value between 4.3 g / ml, 4.4 g / ml, 4.5 g / ml, 4.6 g / ml, 4.7 g / ml, 4.8 g / ml, and 4.9 g / ml.
[0054] Specifically, the specific surface area of the flake-shaped copper powder can be 0.4 m². 2 / g, 0.45m 2 / g, 0.5m 2 / g, 0.55m 2 / g, 0.6m 2 / g, 0.65m 2 / g, 0.7m 2 Any value between / g.
[0055] Specifically, the specific surface area of the spherical copper powder can be 2.5 m². 2 / g, 2.51m 2 / g, 2.52m 2 / g, 2.53m 2 / g, 2.54m 2 / g, 2.55m 2 / g, 2.56m 2 / g, 2.57m 2 / g, 2.58m2 / g, 2.59m 2 / g, 3.0m 2 Any value between / g.
[0056] In this article, tap density, or bulk density of powder after compaction, refers to the density of powder after it has been packed into a specific container and the container has been vibrated to break up the voids in the powder and bring it into a tightly packed state. By measuring tap density, the flowability and porosity of the powder can be determined. It can be calculated by measuring its volume after 1000 vibrations using a BT-301 vibrator.
[0057] Specific surface area refers to the surface area per unit mass of a porous solid material. The commonly used unit is square meters per gram (m² / g). It can be tested using conventional methods, such as GB / T 13390-2008, "Determination of Specific Surface Area of Metal Powders".
[0058] In this application, the electrode further includes copper nanoparticles, which comprise at least two interconnected copper nanoparticles connected by surface contact.
[0059] In this paper, surface contact connection refers to a connection between two adjacent copper nanoparticles having at least two connection points or an overlap between two adjacent copper nanoparticles, wherein the maximum distance between the two connection points or the intersection arc length of the overlap is at least 10% of the diameter of either copper nanoparticle. In this application, the surface contact connection between two copper nanoparticles can be detected or observed by means of, for example, SEM or TEM.
[0060] In this application, nano-copper particles fill the gaps between flake-shaped and spherical copper powders, directly contacting the flake-shaped and spherical copper powders, making the conductive channels between the conductive particles more unobstructed. Moreover, the filling of nano-copper particles makes the electrode structure more compact, significantly reducing the bulk resistance of the electrode and achieving conductivity comparable to that of a silver electrode.
[0061] In this application, the nano-copper particles are linear copper particles formed by at least two connected copper nanoparticles. The nano-copper particles can also be formed by bending and connecting at least two connected copper nanoparticles at a certain angle to form L-shaped, V-shaped, U-shaped, triangular, quadrilateral, W-shaped, or polygonal copper particles with 5 or more sides (polygonal copper particles with 5 or more sides can be pentagonal, hexagonal, heptagonal, etc.), preferably linear copper particles. In this document, the electrode of the same copper paste may simultaneously contain two or more of the following: linear copper particles, L-shaped copper particles, V-shaped copper particles, U-shaped copper particles, triangular copper particles, quadrilateral copper particles, W-shaped copper particles, or polygonal copper particles with 5 or more sides. For example, in some embodiments, the electrode contains linear copper particles, L-shaped copper particles, V-shaped copper particles, U-shaped copper particles, and triangular copper particles. In some embodiments, the electrode contains linear copper particles, L-shaped copper particles, V-shaped copper particles, U-shaped copper particles, and quadrilateral copper particles. In some embodiments, the electrode contains linear copper particles, L-shaped copper particles, V-shaped copper particles, U-shaped copper particles, and pentagonal copper particles. In some embodiments, the electrode contains linear copper particles, V-shaped copper particles, U-shaped copper particles, and triangular copper particles. In some embodiments, the electrode contains linear copper particles, L-shaped copper particles, V-shaped copper particles, U-shaped copper particles, triangular copper particles, and quadrilateral copper particles.
[0062] The nano-copper particles described in this application have a three-dimensional shape with unequal diameters, which facilitates their matching with various shaped gaps formed between multiple flake copper powders. This effectively reduces the gaps formed by the flake copper powders and increases the conductive pathways between the copper powders. Especially for linear, L-shaped, and V-shaped copper particles, compared to spherical copper particles, they have more contact points with flake copper powders and other nano-copper particles along their length, increasing the contact area between flake copper powders and nano-copper particles, and between nano-flake copper powders and copper particles. This increases the conductive pathways between the copper powders, resulting in increased conductivity of the copper paste as an electrode. For triangular, quadrilateral, and polygonal copper particles, their ends have multiple protrusions formed by smaller copper nanoparticles, which act as bridges for electron conduction between the flake copper powders, similarly increasing the conductivity of the electrode.
[0063] Linear copper particles are defined as a string-like structure in which multiple connected copper nanoparticles are arranged in a face-to-face contact along the length direction. For example, when a linear copper particle is composed of two copper nanoparticles, it is gourd-shaped or peanut-shaped.
[0064] A bend-at-a-angle connection refers to multiple interconnected copper nanoparticles being connected in sequential face-to-face contact. In a certain position, the extension directions of two of the three interconnected copper nanoparticles (copper nanoparticle A, copper nanoparticle B, and copper nanoparticle C) are different from the extension directions of the other two interconnected copper nanoparticles, and they have a certain angle. That is, the extension direction of copper nanoparticle A after connecting with copper nanoparticle B is different from the extension direction of copper nanoparticle B after connecting with copper nanoparticle C, and they have a certain angle.
[0065] In the nano-copper particles, the number of copper nanoparticles can be 2, 3, 4, 5, or more, with multiple copper nanoparticles connected in series.
[0066] In this paper, the electrode is obtained by curing copper paste. This application also provides a copper paste comprising copper powder, resin, curing agent, dispersant, and solvent, wherein the copper powder includes flake copper powder and spherical copper powder, the mass ratio of flake copper powder to spherical copper powder is (0.7-2):1, preferably (1.2-1.7):1; the weight parts of the copper powder are 80-92 parts, the weight parts of the resin are 1-20 parts, the weight parts of the dispersant are 1-10 parts, the weight parts of the curing agent are 0.1-5 parts, and the weight parts of the solvent are 2-20 parts.
[0067] The resin is selected from one or more of epoxy resin, phenolic resin, acrylic resin, and polyester resin, preferably epoxy resin.
[0068] The curing agent is selected from one or more of dicyandiamide curing agents, acid anhydride curing agents, and latent imidazole curing agents, such as triethanolamine, blocked isocyanate, 1-butyl-3-methylimidazolium dibutyl phosphate, and Baxton (Lanxess) 7982, preferably a latent imidazole curing agent.
[0069] The dispersant is selected from one or more of polyacrylic acid, polymaleic anhydride, sodium polystyrene sulfonate, castor oil, polyethylene glycol monolaurate, oleylamine, oleic acid, Tween 20, and Tween 80, preferably oleylamine, polyacrylic acid, or a combination thereof, with oleylamine:polyacrylic acid = 1.5-3.
[0070] The solvent is selected from one or more of diethylene glycol butyl ether acetate, terpineol, 2,2,4-trimethyl-1,3-pentanediol diisobutyrate, butyl acetate, ethylene glycol monomethyl ether, propylene glycol monomethyl ether, and 2-methyl-2,4-pentanediol, preferably diethylene glycol butyl ether acetate or 2-methyl-2,4-pentanediol.
[0071] Specifically, in the copper paste, the weight parts of the copper powder can be 80 parts, 81 parts, 82 parts, 83 parts, 84 parts, 85 parts, 86 parts, 87 parts, 88 parts, 89 parts, 90 parts, 94 parts, or 92 parts.
[0072] In the copper paste, the weight parts of the resin can be 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, etc.
[0073] In the copper paste, the curing agent can be present in parts by weight of 0.1 parts, 1 part, 2 parts, 3 parts, 4 parts, 5 parts, etc.
[0074] In the copper paste, the weight parts of the first dispersant can be 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, etc.
[0075] In the copper paste, the solvent can be present in the following weight proportions: 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, etc.
[0076] The mass ratio of the flake copper powder to the spherical copper powder can be 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, or 2:1.
[0077] The surface of raw copper powder contains oxides and impurities, which reduces its conductivity in the electrode. To improve tap density and oxidation resistance, the copper powder can be treated with a passivating agent to passivate a layer of organic matter on its surface. Specifically, the passivation process involves dispersing the copper powder in ethanol, adding the passivating agent, stirring, and then separating and drying to obtain passivating agent-pretreated copper powder. Further, the passivating agent is selected from one or more of the following: saturated / unsaturated fatty acids containing 8-18 carbons, silane coupling agents, PVP, and thiols.
[0078] In the slurry, flake copper powder has a larger contact area with the organic solvent and lower pressure than spherical copper powder, making it easier to float on the slurry surface. Spherical copper powder, on the other hand, fills the gaps in the flake copper powder or settles under the electrodes (e.g., grid lines). For textured or rough surfaces, spherical copper powder is more likely to fill the pores, increasing the contact area between the slurry and the ITO or TCO on the cell surface, thereby reducing resistance and improving the conductivity of the slurry. Dispersants are a type of surfactant, with a hydrophilic group (amino, carboxyl, hydroxyl) at one end and a lipophilic group (alkanes) at the other. In slurries, they can reduce interfacial tension to make the slurry more homogeneous, adjust the viscosity and printability of the slurry, and improve the slurry's screen transfer properties. At the same time, dispersants can form a thin and uniform wetting layer on the surface of copper powder, helping to disperse the copper powder and prevent particle rearrangement. After printing, the flake copper powder will preferentially align, thus making the flake copper powder uniformly and flatly arranged on the grid line surface, enhancing the grid line's oxidation resistance, improving resistivity, and also benefiting the reliability of the component.
[0079] This application achieves optimal electrical performance by mixing dispersants and other organic components in the slurry and adjusting the ratio of flake copper powder to spherical copper powder, thereby coating the surface of the cured electrode with a layer of flake copper powder.
[0080] In the copper paste, the copper powder further includes copper nanoparticles, the description of which can be found in the description of the copper nanoparticles in the aforementioned electrode. The copper nanoparticles can be pre-prepared by reacting copper salts and a reducing agent in solution, and the size and morphology of the copper nanoparticles can be controlled by using a dispersant and by controlling the reaction temperature and heating rate.
[0081] This application also provides a method for preparing the aforementioned electrode, comprising the following steps:
[0082] The aforementioned copper paste is screen-printed onto a substrate, and then cured by heating in a nitrogen atmosphere to obtain the electrode. The curing temperature is typically 100–200°C, for example, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, etc.
[0083] Curing temperatures include 190℃ and 200℃, with curing times ranging from 10 to 60 minutes. For example, options include 10 minutes, 15 minutes, etc.
[0084] 20min, 25min, 30min, 34min, 40min, 45min, 50min, 55min, 60min, etc.
[0085] This application also provides an electrode, wherein it is prepared by the aforementioned copper paste.
[0086] Pre-prepared copper paste is screen-printed onto a solar cell (e.g., HJT / HBC) with a grid line width of 40-120 μm. The paste is then cured in a nitrogen oven at a temperature typically 100-200°C for 10-60 minutes, forming the electrode grid lines. These grid lines can be characterized using SEM. The electrode can be one of the aforementioned electrodes.
[0087] This application also provides a solar cell, which includes the aforementioned electrodes.
[0088] The solar cell is selected from one of the following: BC cell, HJT cell, and perovskite / crystalline silicon tandem cell.
[0089] Example
[0090] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0091] Unless otherwise specified, all materials and reagents used in the following examples are commercially available.
[0092] Example 1
[0093] The electrode preparation method of this embodiment includes the following steps:
[0094] Step 1: Pretreatment of copper powder:
[0095] 1) Stir 100g of raw copper powder in 100ml of ethanol and ultrasonically clean for 1h. Wash the treated copper powder with 200ml of ethanol, centrifuge, discard the supernatant, and dry in a vacuum drying oven at 60℃ for 12h.
[0096] 2) To remove the oxide layer on the surface of the copper powder, take 100g of the copper powder treated in step 1) and add it to 100ml of 0.5mol / L dilute sulfuric acid solution to acid wash the copper powder. Acid wash at 30℃ for 1h. Wash the treated copper powder with 200ml of water 3 times and 200ml of ethanol once until pH=7. Centrifuge and put it into a vacuum drying oven to dry at 60℃ for 12h.
[0097] 3) Take 100g of copper powder treated in step 2) and put it in 100ml of ethanol. Add 2g of oleylamine as a passivating agent and stir at 40℃ for 12h. Wash it three times with 100ml of ethanol and put it in a vacuum drying oven at 60℃ for 12h.
[0098] Step 2: Preparation of slurry
[0099] Take 0.2g of epoxy resin, 0.1g of triethanolamine curing agent, 0.3g of blocked isocyanate, 0.1g of dibutyl imidazole phosphate, 0.1g of oleylamine dispersant, 0.06g of polyacrylic acid, 0.1g of diethylene glycol butyl ether acetate solvent, and 0.17g of 2-methyl-2,4-pentanediol and stir evenly in a glass dish to obtain a mother liquor. Take 7.5g of passivated flake copper powder (diameter D50 of 3μm and thickness D50 of 400nm) and 5g of spherical copper powder (particle size D50 of 400nm) from step one and pour them into the mother liquor. After stirring, pour the mixture into a three-roll mill for rolling and grinding. Adjust the rolling speed to obtain a homogeneous slurry.
[0100] Step 3: After screen printing the slurry, cure it at 170℃ with nitrogen for 30 minutes, and then test the resistivity, contact resistance, and DH5h contact resistance. The electrode parameters of this embodiment are shown in Table 1, and its SEM images are as follows. Figure 7 As shown, by Figure 7 It is known that the surface of the electrode has flake-shaped copper powder, which is arranged at an angle α along the surface of the electrode in contact with it.
[0101] Resistivity was measured using a conductivity meter to determine sheet resistance and line resistance, and a micrometer was used to measure film thickness and line thickness. The results were calculated using a formula. Contact resistance was measured using a TLM (Total Displacement Meter). The DH5h contact resistance was obtained by placing the light-injected solar cell in a constant temperature and humidity chamber at 85°C and 85% humidity for 5 hours, followed by a TLM test. The electrode parameters for this embodiment are shown in Table 1.
[0102] The electrode of Example 2 differs from that of Example 1 in the type of dispersant. All other parameters are the same. The parameters of the electrode in this example are shown in Table 1.
[0103] The electrode of Example 3 differs from that of Example 1 in that the mass ratio of flake copper powder to spherical copper powder in the raw materials is different. All other parameters are the same. The parameters of the electrode in this example are shown in Table 1.
[0104] The electrode in Example 4 differs from the electrode in Example 1 in that the diameter of the sheet-like copper powder is different. All other parameters are the same. The parameters of the electrode in this example are shown in Table 1.
[0105] The electrode in Example 5 differs from the electrode in Example 1 in that it uses different spherical copper powder. All other parameters are the same. The parameters of the electrode in this example are shown in Table 1.
[0106] The electrode of Comparative Example 1 differs from that of Example 1 in that the mass ratio of flake copper powder to spherical copper powder in the raw materials is different. All other parameters are the same. The parameters of the electrode of this comparative example are shown in Table 1.
[0107] The electrode of Comparative Example 2 differs from that of Example 1 in that the mass ratio of oleylamine to polyacrylic acid in the dispersant is different. All other parameters are the same. The parameters of the electrode of this comparative example are shown in Table 1.
[0108] Table 1. Parameters of each embodiment and comparative example
[0109]
[0110]
[0111] Summary: As shown in the table above, the electrode of this application, due to the layer of flake copper powder adhering to its surface, when the projected area of the flake copper powder on the electrode surface after curing occupies 30%-70% of its surface area, utilizes its superior oxidation resistance to adhere to the electrode surface in a near-horizontal or horizontal state, improving the overall oxidation resistance of the electrode when placed in air, and reducing the electrode's resistivity and contact resistance. Simultaneously, due to the shape difference between flake and ball powder, by controlling the surface area ratio of the flake copper powder on the electrode surface, the firmness of the flake powder's adhesion to the surface is improved, ensuring a high copper powder filling rate on the electrode, further reducing the electrode's resistivity.
[0112] Although the embodiments of this application have been described above, this application is not limited to the specific embodiments and application fields described above. The specific embodiments described above are merely illustrative and instructive, and not restrictive. Those skilled in the art can make many other forms based on the guidance of this specification and without departing from the scope of protection of the claims of this application, and these are all within the scope of protection of this application.
Claims
1. An electrode, wherein, The electrode comprises sheet-like copper powder and spherical copper powder, wherein the surface of the sheet-like copper powder is attached to the electrode surface in a substantially horizontal state. The flake-shaped copper powder is arranged at an angle α to the surface of the electrode, where 0°≤α≤45°; The area of the sheet-like copper powder applied to the electrode surface, as projected onto the electrode surface, accounts for 30%-70% of the electrode surface area; The mass ratio of the flake copper powder to the spherical copper powder is (0.7-2):
1.
2. The electrode according to claim 1, wherein, The thickness D50 of the flake copper powder is 100-500 nm, and its diameter D50 is 1-10 μm.
3. The electrode according to claim 1, wherein, The particle size D50 of the spherical copper powder is 100-500 nm.
4. The electrode according to claim 1, wherein, The tap density of the flake copper powder is 4.4~5 g / mL, and the tap density of the spherical copper powder is 4.3~4.9 g / mL.
5. The electrode according to claim 1, wherein, The specific surface area of the flaky copper powder is 0.3~0.8 m². 2 / g, the specific surface area of the spherical copper powder is 2.5~3.0 m² / g. 2 / g.
6. The electrode according to claim 1, wherein, The cross-section of the electrode is trapezoidal or trapezoidal, and the cross-section is perpendicular to the extension direction of the electrode.
7. The electrode according to claim 1, wherein, The electrode is prepared by screen printing.
8. The electrode according to claim 1, wherein, The electrode also includes copper nanoparticles, each comprising at least two connected copper nanoparticles connected in a surface contact manner to adjacent copper nanoparticles.
9. The electrode according to claim 8, wherein, The copper nanoparticles are linear copper particles formed by at least two connected copper nanoparticles, and / or The copper nanoparticles are formed by bending and connecting at least two connected copper nanoparticles at a certain angle to form L-shaped copper particles, V-shaped copper particles, U-shaped copper particles, triangular copper particles, quadrilateral copper particles, W-shaped copper particles, or polygonal copper particles with more than 5 sides.
10. A solar cell, wherein, Includes the electrode as described in any one of claims 1-9.
Citation Information
Patent Citations
Conductive copper paste, electrode and preparation method of conductive copper paste
CN115116650A
Preparation method of solar cell electrode
CN115411148A
